Genes most linked to depression and its possible treatment - Sodre, Eduardo Garcia; Moreira, Kamile Maria Saboia; Galvão, Daniel Studart Corrêa; Dotto, Paulo Henrique Flores; Nunes, Letícia dos Reis; de Almeida, Matheus Henrick Pereira; Fagundes , Thaylisson Davi Silva; de Paiva , Ycaro Martins; de Almeida , Matheus Santos; Fernandes , Laryssa Pixinine Bittencourt; Neto , Luiz José da Rocha; Suguita , Fernando Jyo; et al. (Seven Editora, 2024)
Depression is considered one of the most common and serious psychiatric disorders, according to the World Health Organization (WHO). It stands out as one of the leading causes of disability worldwide, significantly affecting the quality of life of affected individuals. In Brazil, epidemiological studies indicate that the lifetime prevalence of depression affects about 15.5% of the population, an alarming rate that highlights the importance of better understanding this condition. DOI:https://doi.org/10.56238/sevened2024.025-008